Primary pressure standard based on piston-cylinder assemblies. Calculation of effective cross sectional area based on rarefied gas dynamics. (17th August 2016) - Sharipov, Felix; Yang, Yuanchao; Ricker, Jacob E; Hendricks, Jay H
Abstract: Currently, the piston-cylinder assembly known as PG39 is used as a primary pressure standard at the National Institute of Standards and Technology (NIST) in the range of 20 kPa to 1 MPa with a standard uncertainty of 3 × 10 − 6 as evaluated in 2006. An approximate model of gas flow through the crevice between the piston and sleeve contributed significantly to this uncertainty. The aim of this work is to revise the previous effective cross sectional area of PG39 and its uncertainty by carrying out more exact calculations that consider the effects of rarefied gas flow. The effective cross sectional area is completely determined by the pressure distribution in the crevice. Once the pressure distribution is known, the elastic deformations of both piston and sleeve are calculated by finite element analysis. Then, the pressure distribution is recalculated iteratively for the new crevice dimension. As a result, a new value of the effective area is obtained with a relative difference of 3 × 10 − 6 from the previous one. Moreover, this approach allows us to reduce significantly the standard uncertainty related to the gas flow model so that the total uncertainty is decreased by a factor of three.